Learning Outcomes of Creative Entrepreneurship Products and Students 'Emotional Intelligence to Students' Entrepreneurial Interests - Imelda Imelda; Hasan Maksum (Universitas Pendidikan Ganesha, 2020)
The problem in this research is that the students 'interest in entrepreneurship in class XI at SMKN is still low, which is caused by the students' low emotional intelligence and the learning outcomes of students' Creative Entrepreneurship Products, many of which are below the set minimum completeness standards. This study aims to reveal the contribution of learning outcomes of entrepreneurial creative products and emotional intelligence to class XI students' entrepreneurial interest at SMKN. This type of research is quantitative using correlational research methods. The population of this study was students of class XI at SMKN. The sampling technique was proportional random sampling, with a total sample of 75 students. The data analysis technique used is quantitative data analysis techniques. The results of the research are: 1) There is a contribution of learning outcomes of entrepreneurial creative products to the interest in entrepreneurship of class XI students at SMKN by 28.8%, 2) There is a contribution of emotional intelligence to the interest in entrepreneurship of class XI students at SMKN by 48.9%, 3) There is the contribution of learning outcomes of entrepreneurial creative products and emotional intelligence to the entrepreneurial interest of class XI students at SMKN was 52.7%. So, there is a contribution of learning outcomes of Creative Entrepreneurship Products and emotional intelligence to class XI students' entrepreneurial interest at SMKN.